P24 Patient experience of recovering from pneumonia – a qualitative longitudinal interview study. (December 2018) - Ashton, D; Pick, HJ; Bains, M; Lim, WS
Abstract : Introduction: Symptom resolution in community acquired pneumonia (CAP) has been shown to lag behind clinical cure as assessed by healthcare professionals, with return to pre-pneumonia function and general health reported to take over three months. Despite the high burden of disease experienced by patients during recovery, there are scant data on post-hospital needs and interventions in the management of CAP. Therefore, this study aims to capture specific and detailed patient insight, knowledge and experience of their recovery journey with pneumonia in order to inform and direct recommendations to clinical practice and future research studies. Methods: A qualitative longitudinal design was utilised to collect accounts from 15 participants recovering from CAP. Each participant completed 3 semi-structured interviews during recovery (2, 6, and 14 weeks following discharge). Data were analysed using thematic analysis. Results: Three main themes and associated subthemes emerged from the data: 1) Slow recovery from CAP. Participants viewed the slow recovery as a symptom of pneumonia. Expectations of the time taken to recover from CAP often fell short of the actual recovery time. Failure of antibiotics was perceived to be a main cause of slow recovery. 2) Exposing participant vulnerability. Participants disclosed that they had periods in which they experienced vulnerability. The perceived vulnerability to reinfection manifested in anxieties especially with mixing with individuals showing coryzal symptoms. Further vulnerability was grounded in concerns that CAP would cause damage leading to long term health conditions or the fear that pneumonia could either kill them or significantly reduce their life span. 3) Participants support needs. Participants expressed feelings of isolation and an inability to self-manage their pneumonia symptoms post hospital discharge. They expressed a need for further support during recovery beyond the usual support currently offered. Conclusion: This study demonstrates the significant morbidity experienced by patients during recovery; Symptom persistence, anxiety, functional impairment, and healthcare re-consultation rates are high, with marked impact on quality of life. The information reported by patients should be carefully considered and utilised to develop resources and interventions to improve outcomes for patients.